Role of non-coding RNAs in non-aging-related neurological disorders - Vieira,A.S. (2018)
Protein coding sequences represent only 2% of the human genome. Recent advances have demonstrated that a significant portion of the genome is actively transcribed as non-coding RNA molecules. These non-coding RNAs are emerging as key players in the regulation of biological processes, and act as "fine-tuners" of gene expression. Neurological disorders are caused by a wide range of genetic mutations, epigenetic and environmental factors, and the exact pathophysiology of many of these conditions is still unknown. It is currently recognized that dysregulations in the expression of non-coding RNAs are present in many neurological disorders and may be relevant in the mechanisms leading to disease. In addition, circulating non-coding RNAs are emerging as potential biomarkers with great potential impact in clinical practice. In this review, we discuss mainly the role of microRNAs and long non-coding RNAs in several neurological disorders, such as epilepsy, Huntington disease, fragile X-associated ataxia, spinocerebellar ataxias, amyotrophic lateral sclerosis (ALS), and pain. In addition, we give information about the conditions where microRNAs have demonstrated to be potential biomarkers such as in epilepsy, pain, and ALS.